Isolation and Antibacterial Activity by in vitro and in silico Approach of 6-Deoxyjacareubin Compound from Garcinia latissima Miq. Fruit - Neneng Siti Silfi Ambarwati; Berna Elya; Amarila Malik; Yuditya Artha; Islamudin Ahmad; Azminah Azminah; Muhammad Hanafi; Hanita Omar (Indonesian Journal of Chemistry, 2020)
The previous research showed that the fraction C from active extract of Garcinia latissima Miq. fruit was active against Bacillus subtilis. This study aims to isolate and identify the active compound as an antibacterial agent from the fraction C. Fraction C was purified by recrystallization using chloroform and n-hexane solvents and then isolated using preparative-thin layer chromatography-silica gel 60 GF254 to give a yellow compound. The antibacterial activity was determined using microdilution with thiazolyl blue tetrazolium bromide indicator against B. subtilis American Type Culture Collection 6633. The isolate was identified using UV-Vis, IR, MS, Proton Nuclear Magnetic Resonance (1H-NMR) and carbon NMR (13C-NMR), and NMR-2D techniques including HMQC and HMBC. Based on the spectroscopic analysis and literature review, the compound was identified as 6-deoxyjacareubin, which is a new compound from Garcinia latissima Miq. The 6-deoxyjacareubin showed antibacterial activity with MIC value of 156.25 ppm and was categorized as a weak antibacterial agent because the MIC value was more than 100 ppm. According to in silico approach to the docking study, 6-deoxyjacareubin showed similar hydrophobic interaction with several amino acid residues including C2565, C2589, G2484, U2590, and U5588 between a native ligand.